3D printing the next generation of enhanced solid oxide fuel and electrolysis cells. Issue 33 (1st June 2020) - Pesce, Arianna; Hornés, Aitor; Núñez, Marc; Morata, Alex; Torrell, Marc; Tarancón, Albert
Abstract : Improving of SOCs performance by 3D printing are proved, increasing the active area by high-aspect ratio structuration of their components. Abstract : 3D printing of functional materials will revolutionize the energy sector by introducing complex shapes and novel functionalities never explored before. This will give rise to the next generation of enhanced devices ready for mass customization. Among others, electroceramic-based energy devices like solid oxide fuel and electrolysis cells are promising candidates to benefit from using 3D printing to develop innovative concepts that overcome shape limitations of currently existing manufacturing techniques. In this work, a new family of highly performing electrolyte-supported solid oxide cells were fabricated using stereolithography. Conventional planar and high-aspect ratio corrugated electrolytes were 3D-printed with yttria-stabilized zirconia to fabricate solid oxide cells. Corrugated devices presented an increase of 57% in their performance in fuel cell and co-electrolysis modes, which is straightforwardly proportional to the area enlargement compared to the planar counterparts. This enhancement by design combined to the proved durability of the printed devices (less than 35 mV/1000 h) represents a radically new approach in the field and anticipates a strong impact in future generations of solid oxide cells and, more generally, in any solid state energy conversion or storage devices.